The seroconversion rate of QuantiFERON-TB Gold In-Tube test in psoriatic patients receiving secukinumab and ixekizumab, the anti-interleukin-17A monoclonal antibodies. - Chen-Yu Wu; Hsien-Yi Chiu; Tsen-Fang Tsai (PLoS ONE)
Background For psoriatic patients receiving biologics, the concern of tuberculosis (TB) infection exists. Although the TB risk of anti-interleukin (IL)-17A agents is generally considered very low, more real-world data are needed to support the safety. Objectives This study aims to provide the real-world experience of using serial QuantiFERON-TB Gold In-Tube (QFT-GIT) test among patients treated with secukinumab or ixekizumab in Taiwan, an intermediate TB burden country, for the detection of latent TB infection (LTBI) reactivation or newly acquired TB infection. Methods This retrospective review evaluated 100 consecutive patients with psoriasis receiving anti-IL-17A therapies who were checked with at least twice QFT-GIT between 2016 and 2019 in National Taiwan University Hospital, Taipei and Hsin-Chu, Taiwan. Results Among the 100 patients, the baseline QFT-GIT results were negative in 81.0% (81/100), positive in 18.0% (18/100), and indeterminate in 1.0% (1/100) of patients. The overall outcomes in patients receiving at least 6 months of cumulative exposure to anti-IL-17A agents were persistently seronegative in 80 patients (80.0%), persistently seropositive in 14 patients (14.0%), seroconversion in 1 patient (1.0%), seroreversion in 3 patients (3.0%), and others in 2 patients (2.0%). In patients with at least 11 months of cumulative exposure, the seroconversion rate was 1.3% (1/79). The only case with seroconversion had a positive QFT-GIT result previously. No case of TB reactivation or newly acquired TB infection was identified during the follow-up. Conclusions In patients treated with anti-IL-17A monoclonal antibodies for psoriasis, routine serial repeat QFT-GIT testing was associated with lower seroconversion rate compared to real-world data of tumor necrosis factor-α inhibitors and anti-IL-12/23 antibody in Taiwan and in pivotal studies. Because clinical TB symptoms and signs are often preceded by QFT-GIF seroconversion, this result further supports the safety of anti-IL-17A agents in patients with psoriasis for LTBI.